Notice of Retraction: The Effectiveness of the webinar in providing non-traumatic urology emergencies education to medical personnel during COVID-19 pandemic - Kurnia Penta Seputra; Medianto Medianto; Hamdan Yuwafi Naim; Muhammad Adi S.L.; Besut Daryanto (Brawijaya Journal of Urology, 2022)
This article has been retracted by the publisher. ----------------------------------------------------------------------- This article has been retracted at the request of the Authors. The editors and authors have jointly made the decision to retract the paper. Reasonable effort should be made to remove references to this paper. ----------------------------------------------------------------------- Objectives. Basic emergency knowledge is a very important skill for medical personnel. Providing medical information and education is the new challenge in the COVID-19 pandemic situation. Webinar should be considered as one of alternatives to provide and share the knowledge. This study assessed the effectiveness of webinar as a medium to provide information and education in the field of non-traumatic urology emergencies.Methods. A descriptive analytic research design with cross sectional approach was conducted for all participants. The learning outcomes were assessed by comparing the pretest and the post test.Results. A total of 775 participants were included in this study. It showed a significant improvement in average score from pre-test to post-test (p<0.000). It also showed a similar result in almost all of the topics with p<0.005, except for the topic of treatment of urinary retention with p=0.434.Conclusions. The webinar should be considered as one of the effective educational media to provide information and education on non-traumatic urology emergencies for medical personnel during COVID-19 pandemic.